Validity of Short-Term Assessment of Risk and Treatability in the Japanese Forensic Probation Service - Kikuchi, Akiko; Soshi, Takahiro; Kono, Toshiaki; Koyama, Mayuko; Fujii, Chiyo (Frontiers in Psychiatry, 2021)
This study aimed to evaluate the predictive validity and reliability of the Short-Term Assessment of Risk and Treatability (START) in the context of the Japanese forensic probation service. START is a structured professional judgement guide for risk domains concerning negative behaviors such as violence, self-harm, suicide, substance abuse, unauthorized leave, victimization, and self-neglect. In this study, rehabilitation coordinators evaluated community-dwelling patients who were treated under the Medical Treatment and Supervision Act at baseline and followed-up for 6 months. The results revealed that START vulnerability scores significantly predicted self-harm, suicide, physical aggression, substance abuse, and self-neglect. START strength scores predicted physical violence and unauthorized leave. Specific risk estimates predicted physical violence and self-neglect. Risk judgement for future substance use may require adjustments for cultural differences, because of the lower prevalence in Japan. These results suggest that START offers a feasible and valid tool that allows clinicians to plan treatment and promote recovery of forensic patients in Japan.